Seven-year enrichment: macrofaunal succession in deep-sea sediments around a 30 tonne whale fall in the Northeast Pacific - Smith, Craig R; Bernardino, Angelo F; Baco, Amy; Hannides, Angelos; Altamira, Iris (MARINE ECOLOGY PROGRESS SERIES, 2014)
Whale falls cause massive organic and sulfide enrichment of underlying sediments, yielding energy-rich conditions in oligotrophic deep-sea ecosystems. While the fauna colonizing whale skeletons has received substantial study, sediment macrofaunal community response to the geochemical impacts of deep-sea whale falls remains poorly evaluated. We present a 7 yr case study of geochemical impacts, macrofaunal community succession, and chemoautotrophic community persistence in sediments around a 30 t gray-whale carcass implanted at 1675 m in the well-oxygenated Santa Cruz Basin on the California margin. The whale fall yielded intense, patchy organic-carbon enrichment ({>}15{%} organic carbon) and pore-water sulfide enhancement ({>}5 mM) in nearby sediments for 6 to 7 yr, supporting a dense assemblage of enrichment opportunists and chemosymbiotic vesicomyid clams. Faunal succession in the whale-fall sediments resembled the scavenger-opportunist-sulfophile sequence previously described for epifaunal communities on sunken whale skeletons. The intense response of enrichment opportunists functionally resembles responses to organic loading in shallow-water ecosystems, such as at sewer outfalls and fish farms. Of 100 macrofaunal species in the whale-fall sediments, 10 abundant species were unique to whale falls; 6 species were shared with cold seeps, 5 with hydrothermal vents, and 12 with nearby kelp and wood falls. Thus, whale-fall sediments may provide dispersal stepping stones for some generalized reducing-habitat species but also support distinct macrofaunal assemblages and contribute significantly to beta diversity in deep-sea ecosystems.
Keywords: HOV Alvin (Human Occupied Vehicle)